Przestrzeń turystyczno-rekreacyjna Leszna w perspektywie urbanistycznej - Chudak, Mariusz (Tourist-Recreational Areas of Leszno in the Town Planning Perspective, 2008)
The main aim of the paper is to prove - on the example of Leszno - whether and how the introduction of the free market economy rule influences an increasing interest of local self-government in the tourist-recreational areas. Simultaneously one seeks the answer to the question of real chances for the expansion of the tourist sector in the context of town planning projects accepted for realization. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 384-392